Resilience, Intolerance of Uncertainty, Future Anxiety and Mental Well Being among Young Researchers - Satici, Seydi Ahmet; Kutuk, Hasan; Okur, Sinan; Demirci, Ibrahim; Deniz, M. Engin; Satici, Begum; Kayis, Ahmet Rifat; Aksu, M. Cagri; Korun, Ali Berke; Okur, Ezgi; Yilmaz, Fatma Betuel; Birni, Gaye; et al. (SPRINGER, 2025)
Young researchers face significant psychological challenges that may jeopardize their mental health. In order to protect and support the psychological health of young researchers, the determinants of mental well-being should be examined. This study aims to examine the serial mediating roles of intolerance of uncertainty and future anxiety in the relationship between resilience and mental well-being in young researchers. The study sample consisted of 259 female and 146 male doctoral students (Mage = 30.385, SD = 3.062). The research findings revealed that resilience, intolerance of uncertainty, and future anxiety are important predictors of young researchers' mental well-being. The results indicate that resilience positively predicts mental well-being, while intolerance of uncertainty and future anxiety play a partially serial mediating role in this relationship. This finding means that young researchers with low resilience experience more intolerance of uncertainty, which increases their future anxiety and thus leads to a decrease in mental well-being. This result emphasizes the importance of developing resilience in young researchers to reduce the negative effects of uncertainty and anxiety on mental health. Being resilient to navigate uncertain situations and reduce future anxiety is a protective factor for the mental well-being of young researchers. All these findings expand the understanding of the protection of the mental health of young researchers and offer important implications.
Keywords: COST ReMO; Young researchers; Resilience; Mental well-being; Intolerance of uncertainty; Future anxiety; HAPPINESS; HEALTH; SCALE; Psychiatry